Social Responsibility in University Students According to Gender and Age - Palacios Garay, J. Paola (2021)
Aims The university’s social responsibility has a policy of improving university continuity by fulfilling the mission by forming caring citizens, ethical management, environmental care, and disseminating social knowledge. This study aimed to evaluate social responsibility in university students. Instrument & Methods The research was developed under the quantitative approach, substantive type, descriptive level, non-experimental cross-sectional design. It had a sample of 500 university students of the fourth and fifth cycle of a private university’s faculty of health sciences. The instrument was applied to evaluate the characteristics of university social responsibility in university students by Bolio & Pinzón, which consists of seven dimensions: awareness, commitment, controversy with civility, respect for diversity, citizenship, social justice, change. Findings 46.8% presented low levels; 33.6% presented medium levels, and 19.6% presented a high level of university social responsibility; students under 20 years old obtained 27.8% of low level of university social responsibility, and the female gender obtained 42.2% of low level of university social responsibility. Conclusion Social responsibility should be considered within the university as a transversal axis in all subjects in the holistic formation of the university student since its main objective is to contribute to the formation of students through values, teaching, research and internal management.